Pure psychic akinesia with bilateral lesions of basal ganglia. - Laplane, D (1984)
Three patients showed dramatic psychic akinesia after recovery from toxic encephalopathy. They had no or only mild motor disorders. The spontaneous psychic akinesia was reversible when the patient was stimulated, as if there was a loss of self psychic activation. Intellectual capacities were normal. Two patients had stereotyped behaviours resembling compulsions. In all patients CT cans showed bilateral lesions in the basal ganglia, mainly within the globus pallidus.